Social policy of the early 1990s in the conditions of economic reform: directions and ways of solution (Southern Ural). - N. V. Baryshnikova; O. V. Kuznetsova (Гуманитарные и юридические исследования)
Introduction. The historiography of social transformations in the 1990s and early 2000s in Russia should be divided into several stages. The result of each is the transition from active criticism and analysis of the impact of reforms on the social sphere of society to attempts to study methods and directions for changing social policy at federal and regional levels.   The relevance of the problem is based on the lack of a comprehensive study of social transformations in the Southern Urals, which is the purpose of the study.   Materials and Methods. To achieve this goal, comparative-historical and problem-chronological methods were used, as well as the principles of objectivity, consistency and historicism were applied, allowing to reveal the problem in its logical factual sequence, based on documentary sources. The archival funds of the Southern Urals region and the Federal Archives were involved (archival department of the administration of Chelyabinsk (F. 2 – Administration of the city of Chelyabinsk), State Archive of the Russian Federation (F. 10026 - Supreme Soviet of the RSFSR), State Archive of the Orenburg Region (F. 1014 – Orenburg Regional Council of People’s Deputies), United State Archive of the Chelyabinsk Region (F. R-2740 – Chelyabinsk Regional Council of People’s Deputies), Russian State archive of socio-political history (F. 661 – Democratic Party of Russia; F. 664 – Agrarian Party of Russia), Central State Historical Archive of the Republic of Bashkortostan (F. 1684 – Ministry of Labor and Employment of the Republic of Bashkortostan; F. R-169 – Ministry of Social protection of the population of the Republic of Bashkortostan), Documentation Center of the Modern History of the Orenburg Region (F. 371 – Orenburg Regional Committee of the CPSU; F. 8016 – Orenburg Regional Committee of the Trade Union of Workers of Power Plants and the Electrical Industry; F. 8038 – Orenburg Regional Council of Trade Unions). In addition, programs and projects of social transformations in the region were analyzed.   Analysis. The article analyzes the main trends in social policy changes in connection with the transition to market economy. The dynamics is considered on the example of the regions in the Southern Urals (Orenburg, Chelyabinsk regions and Bashkiria). The reasons for the transition from universal to targeted social assistance are revealed. By the example of demographic changes (births and deaths ratio), decrease in industrial production, lowering standard of living at the beginning of market reforms, the range of measures taken at the regional and federal levels to relieve social tension in society is determined: opening funds, creating a social assistance service, training personnel.   Results. The article draws conclusions about the main reason for the failure of many social transformations – the lack of financial support for the new social policy. In the conditions of the growing economic crisis and the increase in the number of the population below the poverty line, the attempt of the state to delegate the decision on financing and providing selective social support to the regions did not entail effective results. An attempt to switch to targeted assistance and the creation of regional funds for social support of the population made it possible to somewhat reduce social tension in the country. It did not solve all social problems of society, creating a dichotomy of the problem: a constant increase in the number of poor people and a simultaneous reduction or unstable financing of social policy.